Razrabotka i sovershenstvovanie sredstv vestibulyarnoi podgotovki sportsmenov s ispol'zovaniem avtonomnykh dinamicheskikh stendov - Sharov, K. B. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The author has developed and engrained in the training process the series of tests for the vestibular system. The training carried out in the autonomous dynamic stand with the application of "self-stimulation" and in the stand with a mechanical drive concerns to means of "adaptive biomanagement". The research with use of the "self-stimulation" can be carried out with the purposes of the clinical diagnostics of a number of diseases, and also for imitation of human physiological signals for the purposes of vestibular metrology. Probably, it will allow to create the individual programs of the "self-stimulation" for the behavior medicine and the elimination of vestibular asymmetries. This technique can be used in the educational process and for the preventive maintenance of the motor illness.